Investigating the risk of metabolic and cardiovascular comorbidities among patients with parathyroid cancer: a nationwide representative cohort study in Taiwan - Ming-Chieh Tsai; Min-Shu Hsu; Hsin-Yin Hsu; Tzu-Lin Yeh; Chun-Ju Chiang; Wen-Chung Lee; Jing-Rong Jhuang; Shih-Ping Cheng; Po-Jung Tseng; Kuo-Liong Chien (BMC Medicine, 2023)
Abstract Background This study aimed to determine whether primary parathyroid cancer patients were associated with increased metabolic and cardiovascular comorbidities in comparison to the general population. Methods We used the National Taiwan Cancer Registry Database to construct a cohort of patients with parathyroid cancer from January 1, 2004, to December 31, 2019. We compared the incidence of hypertension, diabetes mellitus, hyperlipidemia, atrial fibrillation, coronary heart disease, and heart failure with the general population matched based on a propensity score in a one-to-five fashion. Results A total of 72 parathyroid cancer patients and 360 matched general population (mean age: 55 years; 59% women) were included, with different exclusive numbers for each metabolic and cardiovascular comorbidity cohort. The number of cases based on a total of 2347.7 person-years of observation included 53 deaths, 29 hypertension, 9 diabetes, 13 hyperlipidemia, 10 atrial fibrillation, 18 coronary artery disease, and 13 heart failure. According to multivariate analysis, parathyroid cancer remained significantly associated with diabetes [hazard ratio (HR): 9.28; 95% confidence interval (CI): 1.72–50.07], hyperlipidemia (HR: 5.86; 95% CI: 1.61–21.31), and heart failure (HR: 4.46; 95% CI: 1.18–16.84). Sub-distribution of competing mortality events and subgroup analysis showed robust evidence of metabolic and cardiovascular comorbidities. This national cohort study demonstrated that adult parathyroid cancer patients had a significantly higher incidence of diabetes mellitus, hyperlipidemia, and heart failure than the general population. Conclusions An increased risk of metabolic and cardiac comorbidities among parathyroid cancer patients required great caution.